Computational discovery of plant-based inhibitors against human carbonic anhydrase IX and molecular dynamics simulation. Issue 8 (24th May 2021) - Mahmud, Shafi; Rahman, Ekhtiar; Nain, Zulkar; Billah, Mutasim; Karmakar, Sumon; Mohanto, Sumon Chandro; Paul, Gobindo Kumar; Amin, Al; Acharjee, Uzzal Kumar; Saleh, Md. Abu
Abstract: Carbonic anhydrase IX (hCAIX) is a membrane-spanning metalloenzyme, encoded by CA9 gene, which can lead to various carcinomas if upregulated. Due to its overexpression in many cancer tissues, hCAIX has become a promising target for developing anticancer therapeutics. Furthermore, several classes of small-molecules have shown to inhibit the hCAIX expression. In this study, therefore, we screened ( n  = 42) plant-derived compounds to identify the most potent hCAIX inhibitors and to understand their interactions with hCAIX and drug candidacy through in silico approaches. Among all, only three compounds (i.e. fraxoside, scopolin, and xanthone, ) provided higher binding affinity toward hCAIX protein as compared to the native ligand. In standard docking, scopolin showed −4.97 kcal/mol of binding energy with hCAIX while control ligand provided −4.45 kcal/mol. In precise docking, the highest binding affinity was found for fraxoside (−7.67 kcal/mol) as compared to −3.04 kcal/mol of the control. The Gibbs free energy (ΔG) of these potent leads was also consistent and in support of the docking studies. The binding interactions were also found to be stable in dynamics simulation. Furthermore, analysis of protein-protein interactions and co-expression revealed the possible association of CA9 gene with other tumorous genes, especially angiogenesis factor HIF1A which will most likely be affected by the identified inhibitors. With further experimental validation, therefore, these potential inhibitors could be effective against hCAIX protein, thereby, paving the way for prospective anticancer therapeutics. Communicated by Ramaswamy H. Sarma